2020
DOI: 10.1186/s13014-020-01568-6
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-level biological optimisation of prostate IMRT using patient-specific tumour location and clonogen density derived from mpMRI

Abstract: Aims This study aimed to develop a framework for optimising prostate intensity-modulated radiotherapy (IMRT) based on patient-specific tumour biology, derived from multiparametric MRI (mpMRI). The framework included a probabilistic treatment planning technique in the effort to yield dose distributions with an improved expected treatment outcome compared with uniform-dose planning approaches. Methods IMRT plans were generated for five prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…Second, no ground truth is available for assessment of inter-patient registration, making quantification of uncertainty in the registration process difficult. Third, conversion of cross-sectional to volumetric cell density requires linear scaling: one methodology used previously by our research team [50] computes the scaling factor based on estimated clonogenic cell numbers [51]. Fourth, classification of tumour lesions was performed manually by one experienced urological pathologist and may be subject to observer variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, no ground truth is available for assessment of inter-patient registration, making quantification of uncertainty in the registration process difficult. Third, conversion of cross-sectional to volumetric cell density requires linear scaling: one methodology used previously by our research team [50] computes the scaling factor based on estimated clonogenic cell numbers [51]. Fourth, classification of tumour lesions was performed manually by one experienced urological pathologist and may be subject to observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…Building on our previous work, we will demonstrate the process of co-registration of this model with in vivo imaging data to produce biologically optimised dose distributions for external beam RT or brachytherapy applications [55][56][57][58]. Using models for tumour probability and cell density, it is straightforward to derive a map of clonogen density using voxel-wise multiplication [50]. This provides requisite data for radiobiological optimisation of RT dose distributions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hypoxia modelling, the TCP model used in this study has further limitations in describing tumour radiation response. In this study we have chosen to use our previously validated TCP model [ 36 ], a model that we have used in a number of subsequent biologically targeted radiotherapy studies [ 6 , 35 , 54 ]. As in our previous studies, cell-to-cell communication, intrafraction repair and accelerated repopulation were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The second method, which is the topic of the current study, aims to directly optimize the probability of tumor control. This requires conversion of 3D tracer maps to 3D maps of intra‐tumor radiosensitivity 19–24 . Theoretical studies that assumed that any dose level could be delivered to any voxel have shown that, if the radiosensitivity of each voxel is known, DPBN could lead to gains in tumor control probability (TCP) of more than 30 percentage points without increasing normal tissue exposure 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…This requires conversion of 3D tracer maps to 3D maps of intra-tumor radiosensitivity. [19][20][21][22][23][24] Theoretical studies that assumed that any dose level could be delivered to any voxel have shown that, if the radiosensitivity of each voxel is known, DPBN could lead to gains in tumor control probability (TCP) of more than 30 percentage points without increasing normal tissue exposure. 2,3 These gains are very promising, but the gains should be interpreted with caution since they may be affected by multiple patient-specific factors.…”
Section: Introductionmentioning
confidence: 99%